Ex-situ method for toughening glass/epoxy composites by interlaminar films made of polyetherketone cardo and calcium sulfate whisker. (November 2014) - Guo, Zhenhan; Li, Ziquan; Liu, Jinsong; Chen, Mudan; Zu, Qun; Zhang, Yan; Liu, Ying; Chen, Jiankang
Epoxy matrix composites were toughened by introducing films into fiberglass fabric layers based on an ex-situ vacuum-assisted resin transfer molding technique. The mixture films were made of a certain polyetherketone cardo and calcium sulfate whiskers with different mass percent. The toughening mechanism was studied by dynamic mechanical thermal analysis and scanning electron microscopy. The addition of calcium sulfate whisker changed glass transition temperatures of Epoxy Resin (EP) and polyetherketone cardo, indicating that films with calcium sulfate whisker were melting during the curing of epoxy resin and forming the mixture of EP phase, polyetherketone cardo phase, and calcium sulfate whisker between the layers of composites. Meanwhile, the results indicated that calcium sulfate whiskers and fiberglass fabric formed three-dimensional structure between the layers of composites to toughen the composites. The results of the mechanical properties show that the interlaminar shear strength and fracture toughness ( G IC ) were obviously improved meanwhile tensile strength and flexural strength kept stable whether the addition of films or not. Maximum values of the interlaminar shear strength and fracture toughness ( G IC ) were 22% and 95% higher than that of the controlled specimens without films, respectively. The interlaminar mechanical properties improved with the addition of films made of polyetherketone cardo and calcium sulfate whisker, which is benefit for the improvement of whole mechanical properties and wide usage of laminate composites.